GaliSys: Fully integrated software configurable receiver Integrated Circuit(s) (ICs) for GALILEO radio navigation satellite systems and its applications in disaster management and rehabilitation - Telli, Ali; Cetin, Ediz; Kale, Izzet (My University, 2006)
Statistics show that the numbers of natural disasters are on the increase, resulting in increased numbers of human and economic losses. It is therefore, of paramount importance to effectively and efficiently manage a large-scale disaster by utilizing and deploy the Galileo based technology developed for disaster management and rehabilitation. The University of Westminster's, Applied DSP and VLSI Research Group (ADVRG) has been working on a project, called GaliSys, to design, manufacture, test and commission "Fully Integrated Software Configurable Receiver Integrated Circuit(s) (ICs)" for GALILEO Radio Navigation Satellite(s). GaliSys will not only be used in looming disaster early warning systems but also can be used to provide live damage information on highways, airports, railways, pipes and associated essential infrastructure facilities prior to and soon after the disaster which will be of invaluable use to the emergency services. Furthermore, GaliSys may also provide accurate data for observing possible flood risk areas as well as providing means to locate relief and rescue personnel and vehicles in big wild fires. In addition to these, one other application area of GaliSys may be in effective relief provision for refugees in war stricken parts of the world. GaliSys provides a highly integrated, low-power and flexible platform which is readily user configurable to tailor it to the specific applications and needs. In this paper, the GaliSys project together with its possible applications in disaster management and rehabilitation are presented. ©2006 IEEE.
2006 International Conference on Advances in Space Technologies, ICAST --
Keywords: Aerospace industry; Aircraft accidents; Automobile parts and equipment; Computer software; Disaster prevention; Disasters; Electronics industry; Integrated circuit manufacture; Integrated circuits; Occupational risks; Patient rehabilitation; Radio navigation; Radio systems; Railroad transportation; Satellites; Software design; Technology; Well flooding; Application area; Configurable; Damage information; Disaster management; Early warning systems; Economic losses; Emergency services; Flexible platforms; Flood risks; Fully integrated; Galileo; Highly integrated; Infrastructure facilities; International conferences; Low powers; Natural disasters; Navigation-satellite systems; Re search group; Space technologies; Westminster; Wild fires; Accidents